Meta-Analisis Pengaruh Model Pembelajaran Problem Based Learning terhadap Hasil Belajar Peserta Didik SMK - Tasrif, Elfi; Huda, Yasdinul; Rianda, Pedi; Putra, Pirdo Adi (SAFE-Network, 2023)
This study aims to repeat the analysis of learning based on Problem Based Learning in improving the learning outcomes of SMK students. In addition, this article will also produce a literature study that can be used as study material for the future. Meta-analysis is the method used in this study. The analysis is carried out by formulating research problems, tracing relevant research results. Meta-analysis is a statistical technique that combines two or more similar studies to obtain a combination of quantitative data. Judging from the process, meta-analysis is a retrospective observational study, in the sense that the researcher makes data recapitulations without conducting experimental manipulations. The search yielded 20 relevant articles for this study. These articles were articles that had been highly tested and could be used for data expertise. Data were analyzed using descriptive qualitative analysis. The results of the analysis show that Problem Based Learning-based learning is able to improve student learning outcomes from 1.95-71% on average 44.87% or it can be said that problem based learning has quite an effect on student learning outcomes